The effect of thermal therapy on the blood-brain barrier and blood-tumor barrier. (15th July 2020) - Patel, Bhuvic; Yang, Peter H.; Kim, Albert H.
Abstract: The blood-brain and blood-tumor barriers represent highly specialized structures responsible for tight regulation of molecular transit into the central nervous system. Under normal circumstances, the relative impermeability of the blood-brain barrier (BBB) protects the brain from circulating toxins and contributes to a brain microenvironment necessary for optimal neuronal function. However, in the context of tumors and other diseases of central nervous system, the BBB and the more recently appreciated blood-tumor barrier (BTB) represent barriers that prevent effective drug delivery. Overcoming both barriers to optimize treatment of central nervous system diseases remains the subject of intense scientific investigation. Although many newer technologies have been developed to overcome these barriers, thermal therapy, which dates back to the 1890 s, has been known to disrupt the BBB since at least the early 1980s. Recently, as a result of several technological advances, laser interstitial thermal therapy (LITT), a method of delivering targeted thermal therapy, has gained widespread use as a surgical technique to ablate brain tumors. In addition, accumulating evidence indicates that laser ablation may also increase local BBB/BTB permeability after treatment. We herein review the structure and function of the BBB and BTB and the impact of thermal injury, including LITT, on barrier function.